Survival Advantage Associated with Decrease in Stage at Detection from Stage IIIC to Stage IIIA Epithelial Ovarian Cancer. (1st September 2014) - Hoff, John; Baldwin, Lauren; Lefringhouse, Jason; Pavlik, Edward; Miller, Rachel; DeSimone, Christopher; Ueland, Frederick; Tucker, Thomas; Kryscio, Richard; van Nagell, J. R.
Abstract : Objective. The aim of this study was to document the survival advantage of lowering stage at detection from Stage IIIC to Stage IIIA epithelial ovarian cancer. Methods. Treatment outcomes and survival were evaluated in patients with Stage IIIA and Stage IIIC epithelial ovarian cancer treated from 2000 to 2009 at the University of Kentucky Markey Cancer Center (UKMCC) and SEER institutions. Results. Cytoreduction to no visible disease (P < 0 . 0001 ) and complete response to platinum-based chemotherapy (P < 0.025 ) occurred more frequently in Stage IIIA than in Stage IIIC cases. Time to progression was shorter in patients with Stage IIIC ovarian cancer (17 ± 1 months) than in those with Stage II1A disease (36 ± 8 months). Five-year overall survival (OS) improved from 41% in Stage IIIC patients to 60% in Stage IIIA patients treated at UKMCC and from 37% to 56% in patients treated at SEER institutions for a survival advantage of 19% in both data sets. 53% of Stage IIIA and 14% of Stage IIIC patients had NED at last followup. Conclusions. Decreasing stage at detection from Stage IIIC to stage IIIA epithelial ovarian cancer is associated with a 5-year survival advantage of nearly 20% in patients treated by surgical tumor cytoreduction and platinum-based chemotherapy.